How Selective Are Real Wage Cuts? A Micro-Analysis Using Linked Employer-Employee Data - Boris Hirsch; Thomas Zwick (Institute for the Study of Labor (IZA), 2014)
Using linked employer-employee panel data for Germany, this paper investigates whether firms implement real wage reductions in a selective manner. In line with insider-outsider and several strands of efficiency wage theory, we find strong evidence for selective wage cuts with high-productivity workers being spared even when controlling for permanent differences in firms' wage policies. In contrast to some recent contributions stressing fairness considerations, we also find that wage cuts increase wage dispersion among peers rather than narrowing it. Notably, the same selectivity pattern shows up when restricting our analysis to firms covered by collective agreements or having a works council.
Keywords: J30; J31; 330; selectivity; real wage cuts; real wage rigidity; Germany